Effect of chitosan and alginate concentration on physicochemical properties of hydrogel for controlled release fertilizer - Max Michael Samson; Mailin Misson; Wilson Thau Lym Yong; Suryani Saallah; Hesham El Enshasy (Semarak Ilmu Publishing, 2025)
Controlled-release fertilizers (CRFs) are one of the promising components in modern agriculture, offering gradual nutrient release while minimizing environmental impacts. This study investigates the correlation between alginate and chitosan concentrations and hydrogel physicochemical properties. The objective is to assess their viability as materials in controlled-release fertilizers to replace non-biodegradable materials. The hydrogel materials were characterized by swelling, water retention, and hydrogel yield. Additionally, the morphology of the resulting hydrogels was observed at varying chitosan and alginate concentrations (1%, 2% and 3%). The results demonstrate that the 2% (w/v) formulation displayed the greatest swelling and water retention properties, whereas the 3% (w/v) concentrations yielded more hydrogel beads. Morphological analysis revealed differences in beads shape, transparency, and mechanical strength corresponding to the material concentrations. SEM imaging showed a porous structure within the chitosan/alginate hydrogel which can facilitate nutrient diffusion in CRFs. In conclusion, the utilization of alginate and chitosan biopolymers in core-shell hydrogel bead structures presents a promising avenue for the development of environmentally sustainable agriculture, with further optimization and research required to fully assess their long-term effects and biodegradability.